Peran Single Parent Dalam Mempertahankan Ketahanan Ekonomi Keluarga Melalui Usaha Rumah Tangga (Citra Bakery) di Desa Polewali Kecamatan Gantarang Kabupaten Bulukumba - Nurfadillah Irsyam; Muhammad Alim Ihsan (Jurnal Berita Sosial, 2025)
The main research question in this study is how single parents maintain family economic resilience through their home businesses and how they empower the community. The sub-questions in this study are: 1) What steps do single parents take to meet their families' economic needs in Polewali Village, Gantarang District, Bulukumba Regency? 2) What is the impact of a home business (Citra Bakery) run by a single parent on family empowerment in Polewali Village, Gantarang District, Bulukumba Regency? The purpose of this study is to determine the role of single parents in maintaining economic resilience through a home business (Citra Bakery) in Polewali Village, Gantarang District, Bulukumba Regency, and to determine the impact of a home business (Citra Bakery) run by a single parent on family economic empowerment in Polewali Village, Gantarang District, Bulukumba Regency. This study uses a qualitative research method with a phenomenological approach. The data sources in this study are the home business owner and employees of the home business (Citra Bakery). Data collection was conducted through observation, interviews, and documentation. Data management techniques involve processing and analyzing collected data, editing the data, and clarifying its accuracy. The results of this study indicate that the steps taken by single parents are: 1) improving skills or self-potential, 2) building emotional resilience, 3) encouraging economic independence through home-based businesses, and 4) building relationships to gain economic support. The impacts of these businesses are: 1) economic empowerment, 2) skills empowerment, 3) independence empowerment, and 4) social empowerment. The implications of this research are: 1) business owners and employees are expected to continue developing skills, expanding relationships, and managing income independently to improve family stability. 2) business owners and employees are expected to maintain emotional resilience in facing the challenges of business and daily life